Strategi Pencegahan Hoaks Dalam Kampanye Pemilu Ditinjau Dari Prespektif Pidana Dan Dampak Sosial - Roy Marthen Moonti; Saiful R. Pakaya; Rustam Hs. Akili; Yusrianto Kadir; Marten Bunga (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2024)
The aim of this research is to find out how criminal law regulates and recognizes the spread of hoaxes in the context of election campaigns and to find out how prevention efforts and legal education can be improved to reduce the spread of hoaxes during election campaigns. In this research, the researcher used a normative research method, namely a research method that aims to analyze, interpret and evaluate applicable law or legal principles by referring to theory, doctrine, statutory regulations, court decisions and other legal sources. Social media is the easiest place to share and get various information about the latest things that are currently being discussed and paid attention to by the public. However, as explained previously, not everyone can use social media well and wisely. This can be seen from the rise of hoax news spread on various social media platforms, be it Facebook, Instagram, WhatsApp, Twitter and so on.